2020
DOI: 10.1002/psc.3238
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the relationship between structure and antioxidant activity of tripeptides

Abstract: Funding information Kewpie Corporation, JapanPeptides from enzymatic hydrolysates of food proteins exhibit significant antioxidant activity. Several studies have attempted to determine the factors contributing to the antioxidant activity of peptides; however, the physicochemical properties and factors essential for the antioxidant activity of peptides are still unclear. In this study, in order to clarify the factors important for peptide antioxidant activity based on the properties of component amino acids, 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…Experiments conducted by Wu et al also indicated that E HOMO and E-gap were feasible to describe the antioxidant behaviors of a set of man-made peptides, which were designed from the parent peptide “PMRGGGGYHY” [ 41 ]. Consistent with other studies reported [ 44 ], the presence of active residues Tyr, Trp, or Met as well as high E HOMO and low E-gap should be the characteristics of a peptide responsible for inhibiting the oxidation of linoleic acid. Amino acids, Tyr and Trp, act as active sites were also confirmed by Molecular docking.…”
Section: Discussionsupporting
confidence: 91%
“…Experiments conducted by Wu et al also indicated that E HOMO and E-gap were feasible to describe the antioxidant behaviors of a set of man-made peptides, which were designed from the parent peptide “PMRGGGGYHY” [ 41 ]. Consistent with other studies reported [ 44 ], the presence of active residues Tyr, Trp, or Met as well as high E HOMO and low E-gap should be the characteristics of a peptide responsible for inhibiting the oxidation of linoleic acid. Amino acids, Tyr and Trp, act as active sites were also confirmed by Molecular docking.…”
Section: Discussionsupporting
confidence: 91%
“…This implies that some features of amino acids can contribute to antioxidant activity at any position, even though their importance varied with positions. The theoretical conclusion derived from the selected features was also supported by the study of Uno et al 31 …”
Section: Discussionsupporting
confidence: 66%
“…Based on the variable importance values, almost all the feature selection methods showed that the C-terminal residues played the most important role in antioxidant activity, while the central amino acid contributed the least to the activity, which was partly consistent with previous results from wet-chemistry and QSAR studies, where there was no comparison between N- and C- terminals. 12 , 24 , 31 Previous studies were confined to amino acid physicochemical properties (with about 195 indices) or the AADs which could not take full advantage of all the amino acid indices to identify the most representative indices to characterize tripeptides. 8 , 11 , 32 Although some of the selected features, especially non-physicochemical properties (e.g., LIFS790103 stands for “Conformational preference for antiparallel beta-strands”), might be difficult to understand and explain, these selected features are much targeted and less redundant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to predict the bioactivity of peptides, quantitative analysis of the relationship between the structure and bioactivity of peptides has received much interest from many physical biochemists. In a recent study 25 , the hydrophobicity of the amino acid located at the N-terminal end was reported to be more hydrophilic than that of the same amino acid located at both the middle and C-terminal ends. Therefore, it is likely that 4-mer peptides are more hydrophilic than longer peptides, such as 5-, 6-, and 7-mer peptides.…”
Section: Resultsmentioning
confidence: 97%